2013
DOI: 10.1002/ana.23960
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus treatment of refractory epilepsy in tuberous sclerosis complex

Abstract: Objective: Epilepsy is a major manifestation of tuberous sclerosis complex (TSC). Everolimus is an mammalian target of rapamycin complex 1 inhibitor with demonstrated benefit in several aspects of TSC. We report the first prospective human clinical trial to directly assess whether everolimus will also benefit epilepsy in TSC patients. Methods: The effect of everolimus on seizure control was assessed using a prospective, multicenter, open-label, phase I/II clinical trial. Patients 2 years of age with confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
263
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(271 citation statements)
references
References 47 publications
4
263
1
3
Order By: Relevance
“…14 Subsequent studies have yielded similar results. 15,16 Epilepsy is a disabling, longer-term manifestation of TSC, yet long-term outcomes have yet to be assessed.…”
mentioning
confidence: 76%
“…14 Subsequent studies have yielded similar results. 15,16 Epilepsy is a disabling, longer-term manifestation of TSC, yet long-term outcomes have yet to be assessed.…”
mentioning
confidence: 76%
“…Several preclinical studies and early human case reports have demonstrated that mTORC1 inhibitors such as sirolimus or everolimus are useful for treating seizures 39,[51][52][53][54] , whereas more recent prospective trials have shown that benefits could not be demonstrated when seizure frequency was analysed as a secondary outcome measure 55,56 . Moreover, 10-20% of TSC patients showed exacerbation of seizures after everolimus treatment, even in the clinical trial that demonstrated the efficacy of everolimus 57 . Thus, in addition to mTORC1 inhibitors, new approaches for the treatment of neurological symptoms in TSC patients are needed to improve not only seizure control but also cognitive function and patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort of 26 patients, 16 suffered from seizures, and everolimus treatment modestly benefitted nine patients with seizure reduction. A more recent study showed that seizure frequency was reduced in TSC patients treated with everolimus (Krueger et al 2013). In their cohort of 20 patients treated with everolimus, seizure frequency was reduced by 50% in 12 of 20 subjects.…”
Section: Focal Cortical Dysplasia and Tuberous Sclerosis: Paradigm Mtmentioning
confidence: 95%
“…In their cohort of 20 patients treated with everolimus, seizure frequency was reduced by 50% in 12 of 20 subjects. Significant reductions in seizure duration and improvement in parent-reported behavior and quality of life were also observed (Krueger et al 2013). Clearly, mTOR inhibition may provide a novel cell-signaling cascade target in refractory epilepsy.…”
Section: Focal Cortical Dysplasia and Tuberous Sclerosis: Paradigm Mtmentioning
confidence: 95%